Abyad Iyam a multi-modal transport & civic commons - Penaranda, Anna Julia A.
As population increase and more developments occur, cities continue to expand and grow denser each day. This has caused progress and have brought a lot of benefits to communities and places. However, alongside this, rapid urbanization have also caused strains on the economic, environmental, social, cultural aspects and daily lives of people. To prevent these negative effects, specific interventions must be initiated to revitalize and enliven places once again. Each place has its own story, culture and a specific set of problems needed to be addressed. To create effective architectural interventions, the context of each place must be extensively studied, as well as the needs and wants of its people. An agenda would e generated from this process, which shall be addressed by proposing new interventions. This methodology is applied in the creation of this thesis project. The chosen site, Lucena City is a highly-urbanized city rich in history and culture, yet, at present, it is experiencing several issues that can be addressed through an architectural intervention. This study discusses the context of Lucena City, its problems and the agenda that the proposed intervention aims to address; connectivity, local and community building.